Anne of Green Gables - Sullivan, Kevin (Kevin Charles); McDougall, Ian; Follows, Megan; Dewhurst, Colleen; Farnsworth, Richard, 1920-2000; Hamilton, Patricia; Grant, Schuyler; Crombie, Jonathan; Montgomery, L. M. (Lucy Maud), 1874-1942 (Sullivan Entertainment, 2002)
An elderly bachelor and his spinster sister adopt an orphan and are mistakenly sent a girl instead of a boy. The orphan, Anne, remains with the couple, moves from one mishap to another, succeeds academically, and finds love.